FAKTOR INDIVIDU DAN FAKTOR PEKERJAAN YANG MEMPENGARUHI KELUHAN MUSCULOSKELETAL DISORDERS PADA PEKERJA PABRIK KELAPA SAWIT PT AGRINDO INDAH PERSADA - Rusdani; Sukma Sahreny; Aulia Legita Zahari (Universitas Batam, 2026)
ABSTRACT Background: Palm oil mill workers have a heavy work scope that is potentially prone to Musculoskeletal Disorders (MSDs). Musculoskeletal Disorders (MSDs) are disorders of the muscles and bones that often occur due to individual and work factors. Methods: This research uses a cross-sectional study design with total sampling technique involving 41 workers in the palm oil processing section at PT Agrindo Indah Persada. Data were collected through the Nordic Body Map questionnaire to measure the level of MSDs complaints and questionnaires related to individual factors (age, smoking habits, work duration, and body mass index) and work factors (work posture, work duration, and workload). Data analysis was conducted using Chi-Square and Fisher Exact Test statistical tests. Results: The research results show that individual factors such as age (p=0.000) and work duration (p=0.008) are associated with the risk of MSDs. Additionally, work factors such as work posture (p=0.000) and work duration (p=0.000) are related to the risk of MSDs. Conclusion: Individual and work factors play an important role in influencing MSDs complaints among palm oil mill workers. Preventive efforts such as applying ergonomic principles, reducing workload, and regulating work duration are necessary to reduce the risk of MSDs in workers. Keywords: Individual Factors, Work Factors, Musculoskeletal Disorders